Isolation and characterization of phosphate-solubilizing bacterium Pantoea rhizosphaerae sp. nov. from Acer truncatum rhizosphere soil and its effect on Acer truncatum growth - Ma, Qinghua; He, Shanwen; Wang, Xing; Rengel, Zed; Chen, Lin; Wang, Xinghong; Pei, Shunxiang; Xin, Xuebing; Zhang, Xiaoxia (Frontiers in Plant Science, 2023)
Acer truncatum Bunge, widely distributed in North China, shows excellent tolerance to low-P soils. However, little information is available on potential phosphate-solubilizing bacterial (PSB) strains from the A. truncatum rhizosphere. The objectives of this work were to isolate and characterize PSB from A. truncatum rhizosphere soil and to evaluate the effect of inoculation with the selected strain on A. truncatum seedlings. A Gram-negative and rod-shaped bacterium, designated MQR6 T , showed a high capacity to solubilize phosphate and produce indole-3-acetic acid (IAA) and siderophores. The strain can solubilize tricalcium phosphate (TCP) and rock phosphate (RP), and the solubilization of TCP was about 60% more effective than RP.Phylogenetic analyses based on the 16S rRNA gene and whole-genome sequences revealed that strain MQR6 T formed a distinct phyletic lineage as a new species within the genus Pantoea. The digital DNA-DNA hybridization value between strain MQR6 T and the closely related strains was 19.5-23.3 %. The major cellular fatty acids were summed feature 3 (C16:1ω7c and/or C16:1ω6c), summed feature 8 (C18:1ω6c and/or C18:1ω7c), C14:0, C16:0, and C17:0 cyclo. Several genes related to IAA production, phosphonate transport, phosphate solubilization and siderophore biogenesis were found in the MQR6 T genome. Furthermore, inoculation with the strain MQR6 T significantly improved plant height, trunk diameter, dry weight and P accumulation in roots and shoot of A. truncatum seedlings compared to non-inoculated control. These plant parameters were improved even further in the treatment with both inoculation and P fertilization. Our results suggested that MQR6 T represented a new species we named Pantoea rhizosphaerae, as a plant growth-promoting rhizobacterium that can solubilize inorganic P and improve growth of A. truncatum seedlings, emerging as a potential strategy to improve A. truncatum cultivation.